Development of a new CO2-based Demand-controlled Ventilation Strategy Using EnergyPlus - Chenari, Behrang (2017)
A significant amount of energy is being used by ventilation and air conditioning systems to maintain the indoor environmental condition in a satisfactory and comfortable level. Many buildings, either new or existing (throughout their renovation process) are subjected to energy efficiency requirements but these must not be in the expenses of indoor environmental conditions. For instance, indoor air quality (IAQ) has to be considered while improving energy efficiency, otherwise occupants might be exposed to inappropriate indoor environment. Demand-controlled ventilation (DCV) is a method that provides comfortable IAQ level with lowest energy use. In this paper, the main objective is developing a new CO2-based DCV strategy and simulating it using EnergyPlus. The IAQ and energy consumption associated to this strategy have been compared with the results of CO2-based DCV strategies previously developed by the same authors in another article. The comparison shows that the new strategy performs better, both in energy use and IAQ. The recorded energy savings ranged between 6-14% comparing with the previously developed strategies while IAQ slightly improved.